Synthesis, antibacterial and antifungal activity of some new thiazolylhydrazone derivatives containing 3-substituted cyclobutane ring - Cukurovali, A; Yilmaz, I; Gur, S; Kazaz, C (Elsevier France-Editions Scientifiques Medicales Elsevier, 2006)
A series of Schiff bases, combining 2,4-disubstituted thiazole and cyclobutane rings, and hydrazone moieties in the same molecule, was synthesized, characterized and evaluated for screening antibacterial and antifungal activities on microorganisms, respectively, on four bacteria and Candida tropicalis. The structures of original compounds were confirmed by analytical and spectroscopic (FT-IR, H-1 NMR and C-13 NMR) methods and elemental analysis. Both the antibacterial and antifungal activities and MIC values of compounds were reported. Among the tested compounds, the most effective compound providing a MIC value of 16 mu g ml(-1) are 2 against C. tropicalis and Bacillus subtilis and 3 against B. subtilis only. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: cyclobutane; thiosemicarbazone; antibacterial activity; antifungal activity; MIC